Financial statement audits: the effect of the 2008 financial crisis on risk assessment and auditors' responses to audits of financial statements in Greece. (29th February 2020) - Dritsas, Stamatios; Petrakos, George
The aim of this paper is to examine (a) the impact of the 2008 financial crisis in Greece on risk assessment, and (b) auditors' responses to specific identified risks to audits of financial statements carried out in this country during the last decade. The study was based on data collected through a statistical survey among experienced statutory auditors employed by five big international audit firms in Greece, in the course of audits of financial statements of commercial and manufacturing private entities located in the country, during the periods before and after the 2008 financial crisis. The empirical research found that the changes in the Greek business environment due to the recent financial crisis, substantially affected the assessment of the risk of material misstatement at financial statement and assertion levels. In addition, the research concluded that inherent and control risk at assertion level would not be considered as independent components of the risk of material misstatement.